1995
DOI: 10.1002/hep.1840210330
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of sinusoids into capillaries in a rat model of selenium-induced nodular regenerative hyperplasia: An immunolight and immunoelectron microscopic study

Abstract: The oral administration of selenium (Se) to young rats induces, over a 2-month period, the formation of nodular regenerative hyperplasia with sinusoidal damage around nodules. Perinodular areas located in zone 1 comprise atrophic hepatocytes and capillarized sinusoids without fibrosis. We used this unique model of capillarization without fibrosis to investigate the temporal relationship between the process of capillarization and changes occurring in the deposition of components of the extracellular matrix. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…The main distinction is that there is no increase in vessel number due to the anatomic constraints of the liver sieve plates. Capillarization of LSEC results in ultrastructural phenotypic conversion to endothelial cells with tight intercellular junctions and loss of fenestrations (Couvelard et al, 1993;Dubuisson et al, 1995;Xu et al, 2003). In multiple human and animal studies, capillarization has been demonstrated to precede alcohol-induced liver disease, portal hypertension, cirrhosis, and chronic hepatitis (DeLeve et al, 2004;Dubuisson et al, 1995;Tsuneyama et al, 2003;Xu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main distinction is that there is no increase in vessel number due to the anatomic constraints of the liver sieve plates. Capillarization of LSEC results in ultrastructural phenotypic conversion to endothelial cells with tight intercellular junctions and loss of fenestrations (Couvelard et al, 1993;Dubuisson et al, 1995;Xu et al, 2003). In multiple human and animal studies, capillarization has been demonstrated to precede alcohol-induced liver disease, portal hypertension, cirrhosis, and chronic hepatitis (DeLeve et al, 2004;Dubuisson et al, 1995;Tsuneyama et al, 2003;Xu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Capillarization of LSEC results in ultrastructural phenotypic conversion to endothelial cells with tight intercellular junctions and loss of fenestrations (Couvelard et al, 1993;Dubuisson et al, 1995;Xu et al, 2003). In multiple human and animal studies, capillarization has been demonstrated to precede alcohol-induced liver disease, portal hypertension, cirrhosis, and chronic hepatitis (DeLeve et al, 2004;Dubuisson et al, 1995;Tsuneyama et al, 2003;Xu et al, 2003). Increased SEC membrane PECAM-1 protein expression and deposition of a laminin-1-containing basement membrane are hallmarks of capillarization in injured livers (Couvelard et al, 1993;DeLeve et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subendothelial matrix deposition (in the space of Disse) leads to incomplete basement membranes ("capillarization") [10,11], which hinder bidirectional exchange processes between hepatocytes and sinusoidal blood stream, and, thus, impairs the clearance function and the biosynthetic delivery function of the parenchymal tissue. Furthermore, narrowing of the sinusoidal lumen by perisinusoidal fibrosis is considered to be a contributing factor to intraparenchymal hemodynamic resistance (portal hypertension).…”
Section: Fibrosis Fibrogenesis and Fibrolysismentioning
confidence: 99%
“…Similarly, in an animal model of hepatocarcinogenesis, sequential observation of the sinusoids within the tumor nodule demonstrated that the endothelial cells began to express FVIII-RAg and the number of Kupffer cells decreased as the arterial blood supply increased (Yamamoto et al 1996;Shoji et al 1994). FVIII-RAg expression in the sinusoids indicates sinusoidal capillarization (Schaffner and Popper 1963), which has also been observed in selenium-induced hepatic lesions (Dubuisson et al 1995). Therefore, FVIII-RAg expression and the lack of Kupffer cells in the hepatic sinusoids in the present study may also suggest that the main route of blood supply to the liver in cases with advanced LGL leukemia was the hepatic artery.…”
mentioning
confidence: 88%